THE FIRST RENAL ARTERY THROMBOSIS TREATMENT WITH PERCUTANEOUS ANGIOPLASTY IN THE REPUBLIC OF KOSOVO: CASE REPORT - Trjacheski, Ted; Olluri, Elmi; Sulovari, Admir; Xhafa, Ajet; Krasniqi, Suzana; Sejdiu, Imer; Tolaj, Miloreta; Olluri, Elton; Martinaj, Nazmije; Rama, Blerta; Brovina, Lulzim (Journal of Morphological Sciences; Vol 4 No 3 (2021): JMS, 2021)
Renal artery thrombosis is organ-threatening condition, which is not easy to be recognized. We present the first case of acute renal thrombosis treated with percutaneous angioplasty in the Republic of Kosovo, diagnosed in a public and successfully treated in a private institution as a result of integrated healthcare system. Keywords: renal artery thrombosis, percutaneous angoplastu, sten, thrombus aspiration. https://doi.org/10.55302/JMS2143021t